Предмет: Алгебра,
автор: RoseTayler
6х(х-3.5)- 2х(3х+2)=25
Ответы
Автор ответа:
0
6х(х-3.5)- 2х(3х+2)=25
6x(x-3.5)-2x(3x+2)-25=0
(6x)(x-3.5)-(2x)(3x+2)-25=0
(6x²-21x)-(6x²+4x)-25=0
6x²-21x-6x²-4x-25=0
-25x-25=0
-25x=25
25x=-25
x=(-25)÷25
x=-1
6x(x-3.5)-2x(3x+2)-25=0
(6x)(x-3.5)-(2x)(3x+2)-25=0
(6x²-21x)-(6x²+4x)-25=0
6x²-21x-6x²-4x-25=0
-25x-25=0
-25x=25
25x=-25
x=(-25)÷25
x=-1
Похожие вопросы
Предмет: Английский язык,
автор: tanasepilevic12
Предмет: Математика,
автор: buholceva336
Предмет: Обществознание,
автор: hnltq14
Предмет: Математика,
автор: tulina2004
Предмет: Математика,
автор: gorbunova85